(untitled) (Fiep Bulletin - online, 2017)
The present work deals with the Quality of Life at Work in the professional Bricklayer in large works in the city of PontaGrossa, state of Paraná. For the evaluation, the questionnaire Quality of Working Life Questionnaire (QWLQ - 78) was used,consisting of 78 (seventy - eight) questions distributed in 4 (four) domains. The sample consisted of 19 (nineteen) professionalsand after tabulation of the data, they were treated by descriptive statistics, which demonstrated that the physical/health domainand psychological domain are most affected by the generally unhealthy working conditions offered for these professionals.